Evaluation of serum cardiac biomarkers in sheep with acute lactic acidosis - FARTASHVAND, M.; HAJI-SADEGHI, Y. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study we investigated the changes of cardiac injury biomarkers in serum samples from 200 sheep with acute ruminal lactic acidosis (ARLA) and 50 healthy controls belonging to the Ghezel breed. After clinical examination and recording of vital signs (heart rate, respiratory rate, rectal temperature and hydration status), rumen fluid and venous blood samples were collected. The pH of rumen fluid was determined using a paper tape pH-meter and lactic acid concentration of serum was measured using a commercially available method. Similarly, activities of AST, LDH, CK-MB and serum concentration of cTnI were measured using special commercial kits. According to the findings serum activities of AST (p = 0.007) and CK-MB (p = 0.002) in sheep with ARLA were significantly higher than in healthy animals. Serum LDH activity in the disease group was higher than in the control group, however this difference was statistically non-significant. cTnI concentration were 0.684 ± 0.03 ng/ml in sheep with ARLA, which was significantly higher than in healthy sheep (p = 0.000). There were significant negative correlations between ruminal pH and serum lactate levels, heart rate, respiratory rate and dehydration degree. The sheep with the lowest ruminal pH (3 cases with < 4.5) had the highest levels of cTnI (2.28 to 3.06 ng/mL), and all died. It can be concluded that lactic acidosis may cause some degree of heart damage, although further studies are needed to support this speculation.